Does the menopausal status of female gynecologists affect their prescription of menopausal hormone therapy?. (3rd July 2016) - Vallejo, M. S.; Witis, S.; Ojeda, E.; Mostajo, D.; Morera, F.; Meruvia, N.; Martino, M.; Lima, S.; Espinoza, M.T.; Castillo, O.; Campostrini, B.; Danckers, L.; et al.
Abstract: Objective: To evaluate whether menopausal status and symptoms among female gynecologists would influence their clinical behavior related to menopausal hormone therapy (MHT). Methods: Female gynecologists of 11 Latin American countries were requested to fill out the Menopause Rating Scale and a questionnaire containing personal information and that related to MHT use. Results: A total of 818 gynecologists accepted to participate (86.4%). Overall, the mean age was 45.0 ± 10.7 years, 32.2% were postmenopausal, and 17.6% worked in an academic position; 81.8% reported that they would use MHT if they have symptoms, regardless of menopausal status. Academic gynecologists favor personal MHT use at a higher rate ( p = 0.04) and have a higher MHT prescription rate as compared to non-academic ones ( p = 0.0001). The same trend was observed among post- as compared to premenopausal ones ( p = 0.01) and among those who had hysterectomy alone as compared to those experiencing natural menopause ( p = 0.002). The presence of menopausal symptoms did not influence their MHT prescription. Current use of MHT and alternative therapy was higher among post- than premenopausal gynecologists (both, p  = 0.0001) and among those who had undergone hysterectomy than those experiencing natural menopause. A 38.5% perceived breast cancer as the main risk related to MHT, and a high proportion prescribed non-hormonal drugs (86.4%) or alternative therapies (84.5%). Conclusion: Most female gynecologists in this survey would use MHT if menopausal symptoms were present. Postmenopausal physicians use MHT and prescribe it to their symptomatic patients at a higher rate than premenopausal physicians.